New Insights into the Distribution and Evolution of WNW-Directed Faults in the Liaodong Bay Subbasin of the Bohai Bay Basin, Eastern China - Li, Wei; Meng, Meifang; Zhang, Tongjie; Chen, Xingpeng; Liu, Yiming; Wang, Di; Yang, Haifeng; Niu, Chengmin (Frontiers in Earth Science, 2022)
WNW-directed faults are widespread in eastern China, but dispute about their distribution and the evolutionary processes remains unsettled. Based on the latest 3-D seismic data, a fault array including a number of WNW-directed in the south of Liaodong Bay sub-basin was identified, of which the evolution and formation mechanism were discussed. The results show that four WNW-directed faults are characterized by poor continuity, nearly-parallel arrangement. Vertically they display a listric geometry and cut through the Paleozoic and Mesozoic formations. Since the late Triassic, the studied faults initiated as reverse faults under the nearly S-N horizontal compression. During the Jurassic, those faults kept their reversing activity with a dramatically decreased intensity. During the early Cretaceous, the WNW-directed faults turned into normal faults under the regional extension and got inflenced by sinistral strike-slip of the Tan-Lu fault zone. During the late Cretaceous, the WNW-directed normal faults probably stopped faulting due to the regional compressional event. During the Paleogene the WNW-directed faults reactivated with a decreased intensity and got cut by the NNE-directed faults. The newly identified WNW-directed faults have a regional tectonic significance, we speculate that the WNW-directed faults in the Liaodong Bay sub-basin can extend westerward to the Yanshan Orogenic Belt, and it could provide evidence for the existence of the large-scale Jining-Shangyi-Pingquan-Qinhuangdao-Lvshun fault zone in the northern margin of North China Block. The development of the WNW-directed faults in the south of the Liaodong Bay sub-basin is conducive to the formation of the Mesozoic and Paleozoic buried hills and the hydrocarbon accumulation. Besides, we suggest that the compressional segment of the conjugated strike-slip transition zone formed by the interaction of the WNW- and NNE-directed strike-slip faults is conducive to hydrocarbon accumulation.